Influence of Loading Time of a Load Plate and Sample Size on the Measurement of Physical Properties of Resilient Materials - KIM, Kyoung woo; YEON, Jun oh; YANG, Kwan seop; KIM, Myung jun (Archives of Acoustics, 2015)
This study investigates several factors that have not been specified in the standard for dynamic stiffness, compressibility, and long-term deformation; these factors can be used to evaluate the acoustic and physical performances of resilient materials. The study is intended to provide basic data for deriving the factors that need to be additionally reviewed through the standards. Since magnitude of dynamic stiffness changes with an increase in loading time, it is necessary to examine the setting of the loading time for a load plate under test conditions. Samples of size 300×300 mm, rather than 200×200 mm, yielded more reliable results for compressibility measurement. Since the test to infer long-term deformation of resilient materials after a period of 10 years in some samples showed variation characteristics different from those specified in the standards, it is recommended that the test method should be reviewed through ongoing research.